Analysis of Functional and Neutral Differential Equations via Lyapunov Functionals - Raffoul, Youssef N. (Journal of Advances in Applied & Computational Mathematics, 2023)
We employ Lyapunov types functions and functionals and obtain sufficient conditions that guarantee the boundedness and the exponential decay of solutions, stability and exponential stability of the zero solution in nonlinear delay and neutral differential systems. The theory is illustrated with several examples. 2000 Mathematics Subject Classification: Primary 39A13, 39A23; Secondary 34K42